Philosophical basics of ecology and economy - Faber, Malte; Manstetten, Reiner (Routledge, 2010)
The distinctive characteristic of this book's approach is to provide a brand new and comprehensive view on problems pertaining to the relationship between humans and nature, without limit to any one particular discipline. Environmental issues are not exclusively physical, biological, economical, political, social, or cultural problems. They are rather all these and more
Includes bibliographical references and indexes
Keywords: Umwelterziehung; Umweltethik; Ressourcenökonomie